2019
DOI: 10.1088/1361-648x/ab04d7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of beryllium oxide irradiated by deuterium ions: sputtering and reflection

Abstract: The sputtering and reflection properties of wurtzite beryllium oxide (BeO) subjected to deuterium (D) ions bombardment at 300 K with ion energy between 10 eV and 200 eV is studied by classical molecular dynamics. Cumulative irradiations of wurtzite BeO show a D concentration threshold above which an 'unphysical dramatic' sputtering is observed. From the cumulative irradiations, simulation cells with different D concentrations are used to run non-cumulative irradiations at different concentrations. Using a D co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…For these interactions, D atoms are considered as H atoms with a mass of 2.014 atomic mass units. The Be-Be and Be-H potential are both taken from [12] (version II), the H-H potential is taken from [13], the O-O is taken from [14], the Be-O is taken from [15] and the O-H part is taken from [8]. The full Be-O-H potential was previously shown to give good agreement between simulated and experimental sputtering yields [8], and is therefore well-suited for plasma-wall interaction simulations.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For these interactions, D atoms are considered as H atoms with a mass of 2.014 atomic mass units. The Be-Be and Be-H potential are both taken from [12] (version II), the H-H potential is taken from [13], the O-O is taken from [14], the Be-O is taken from [15] and the O-H part is taken from [8]. The full Be-O-H potential was previously shown to give good agreement between simulated and experimental sputtering yields [8], and is therefore well-suited for plasma-wall interaction simulations.…”
Section: Methodsmentioning
confidence: 99%
“…In [8], it is shown that the sputtering yield increases with c D in the material. The best comparison between MD and experimental sputtering yields is obtained at 300 K for c D ≈ 0.12 atomic fraction (at.fr.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations